Pembentukan Nilai-nilai Karakter Islami Siswa Melalui Metode Pembiasaan (Studi Kasus di SDN Babakan Sirna Kota Sukabumi) - Inar Suminar; Helmawati Helmawati; Listia Maliahani; Darus Darus (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The education is the important actor to ensure national live continuity. Many of criminal case, student fight, underage rapes, drugs disseminating, and corruptions case was the indicator of moral degradation. Therefore, character and personality building by including religion values have to be applied. Refraction method in character and personal building is the important act to prevent those morals degradation. Children’s characteristic values will grow and develop positively appropriate with Islamic education teach, if school’s environment and children’s live domain espouse children growth with any goodness. This paper aims to reveal students Islamic characteristic values establishment by refraction method in SDN Babakan Sirna Sukabumi, by including sub focus in: (1) Aims of Islamic characteristic values establishment by refraction method in SDN Babakan Sirna Kota Sukabumi. (2) How is refraction form to establish Islamic characteristic values in SDN Babakan Sirna Sukabumi. (3) How is the evaluation system, and what character shaped in student’s personality by refraction method in SDN Babakan Sirna Sukabumi. (4) What is endorsement and obstacle factor to establish student’s Islamic characteristic values by refraction method in SDN Babakan Sirna Sukabumi.